Multiphase fluid behaviour and thermal characteristics in flow through heated curved ducts - Chandratilleke, Tilak; Nadim, Nima; Narayanaswamy, Ramesh (HEFAT, 2012)
Fluid flow and thermal characteristics in curved ducts are influenced by the secondary flow effects arising from duct curvature and are uniquely different to those in straight ducts. Such flows stimulate fluid mixing to promote wall heat transfer even in laminar flow and exhibit hydrodynamic instability under certain flow conditions. This paper provides an overview of the present knowledge-base in the field for analysing and designing technological systems with embedded curved flow geometries. It then discusses the details and outcomes of a research programme covering both single and two-phase flow behaviour in curved ducts. As a key contribution to the field, the study develops and validates a novel numerical process based on three-dimensional vortex structures (helicity) and a curvilinear mesh system that overcomes previous modelling limitations. For both single and two-phase flow situations, computations are performed to examine the flow characteristics within rectangular, elliptical and curved ducts and, to recognise parametric influences. These are effectively deployed for physical interpretation and illustration of unique features in single and two-phase flow processes within curved ducts. The study introduces a unified approach for identifying the onset of secondary flow instability directly within the computational process. An entropy-based analysis is appraised in the study for optimising curved duct thermal characteristics.